1994
DOI: 10.1159/000204238
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Protoporphyrin and Iron Deficient Erythropoiesis

Abstract: Iron-deficient erythropoiesis may occur in patients with adequate levels of storage iron as well as those with tissue iron deficiency. Here we compare two methods of detecting iron-deficient erythropoiesis. The measurement of percent hypochromic cells in the full blood count provides a direct indicator of iron-deficient erythropoiesis. The zinc protoporphyrin (ZPP) determination is simple, precise and reproducible, and also appears to provide a sensitive index of iron-deficient erythropoiesis. There was a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 4 publications
0
9
0
3
Order By: Relevance
“…Because this phenotype is not normally observed in cells, it is reasonable to extrapolate from the present work that iron control of heme biosynthesis is a general regulatory phenomenon found in other organisms. Humans with iron deficiency anemia show a 5-fold increase in blood protoporphyrin, reaching approximately 2 ϫ 10 Ϫ4 mol/ mol of heme (38). This elevated level is modest by comparison with the B. japonicum irr mutant, which accumulates approximately 15 mol of protoporphyrin/mol of heme under iron limitation (by recalculation of the data in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because this phenotype is not normally observed in cells, it is reasonable to extrapolate from the present work that iron control of heme biosynthesis is a general regulatory phenomenon found in other organisms. Humans with iron deficiency anemia show a 5-fold increase in blood protoporphyrin, reaching approximately 2 ϫ 10 Ϫ4 mol/ mol of heme (38). This elevated level is modest by comparison with the B. japonicum irr mutant, which accumulates approximately 15 mol of protoporphyrin/mol of heme under iron limitation (by recalculation of the data in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…When ZPP is measured in whole blood, falsely elevated values are observed in dialysis patients as well as in the presence of bilirubin and various drugs. Removing these interferences requires careful washing of the RBCs, rendering this assay inappropriate for routine clinical care 172,173 . Erythrocyte ZPP is elevated in the presence of lead poisoning.…”
Section: Erythrocyte Zinc Protoporphyrinmentioning
confidence: 99%
“…A problem with fluorimetric measurement of ZPP arises from the presence of fluorescent compounds in plasma, and values obtained on washed cells are almost always lower than those on whole blood 30. The proportional differences between paired measurements found in this study were similar to those reported elsewhere in subjects free of disorders associated with spuriously raised whole blood ZPP values,30 indicating that most if not all raised values were genuine, including those found in children with proven or probable α-thalassaemia trait. As expected, the plasma effect was greatest in the iron-sufficient group, which had the lowest ZPP values, and least in the iron deficiency anaemia group.…”
Section: Discussionmentioning
confidence: 99%